Different Chondrogenic Potential among Human Induced Pluripotent Stem Cells from Diverse Origin Primary Cells. (21st January 2018) - Rim, Yeri Alice; Nam, Yoojun; Park, Narae; Jung, Hyerin; Jang, Yeonsue; Lee, Jennifer; Ju, Ji Hyeon
Abstract : Scientists have tried to reprogram various origins of primary cells into human induced pluripotent stem cells (hiPSCs). Every somatic cell can theoretically become a hiPSC and give rise to targeted cells of the human body. However, there have been debates on the controversy about the differentiation propensity according to the origin of primary cells. We reprogrammed hiPSCs from four different types of primary cells such as dermal fibroblasts (DF, n = 3 ), peripheral blood mononuclear cells (PBMC, n = 3 ), cord blood mononuclear cells (CBMC, n = 3 ), and osteoarthritis fibroblast-like synoviocytes (OAFLS, n = 3 ). Established hiPSCs were differentiated into chondrogenic pellets. All told, cartilage-specific markers tended to express more by the order of CBMC > DF > PBMC > FLS. Origin of primary cells may influence the reprogramming and differentiation thereafter. In the context of chondrogenic propensity, CBMC-derived hiPSCs can be a fairly good candidate cell source for cartilage regeneration. The differentiation of hiPSCs into chondrocytes may help develop "cartilage in a dish" in the future. Also, the ideal cell source of hiPSC for chondrogenesis may contribute to future application as well.